2012
DOI: 10.1016/j.whi.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

College Graduation Reduces Vulnerability to STIs/HIV among African-American Young Adult Women

Abstract: African-American women are disproportionately affected by STIs including HIV. The Theory of Gender and Power (TGP) posits that economic exposures, including educational attainment, place women at increased risk for STIs/HIV. This study examined the association between educational attainment and vulnerability to STIs/HIV, as well as potential TGP-driven mediators of this association, among African-American women. Baseline data were assessed from an STI/HIV prevention intervention for African-American women (N=8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 36 publications
4
38
1
Order By: Relevance
“…Additionally, previous research has indicated that African-American women with higher educational attainment may be at lower risk for STDs and HIV. 18 Thus, women with higher educational attainment may perceive themselves to be at lower risk for HIV and, consequently, less interested in adopting PrEP as an HIV prevention strategy. These findings are congruent with the recent FDA licensure of PrEP for individuals, including men and women, at high risk for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research has indicated that African-American women with higher educational attainment may be at lower risk for STDs and HIV. 18 Thus, women with higher educational attainment may perceive themselves to be at lower risk for HIV and, consequently, less interested in adopting PrEP as an HIV prevention strategy. These findings are congruent with the recent FDA licensure of PrEP for individuals, including men and women, at high risk for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have examined the link between educational attainment and HIV/STI risk in the USA have provided mixed evidence. Some studies find a protective association, 30,31 other studies find no associations, [32][33][34] and others find education is associated with increased risk. 35 Our results demonstrate that analyses of the association between HIV/STI-related behaviors and women's SES can yield different results depending on whether SES is measured in absolute terms or relative to the male partner.…”
Section: Sensitivity Analysis and Falsification Testsmentioning
confidence: 99%
“…Black women are 20 times more likely to be infected with HIV than women in other racial/ethnic groups [25]. HIV incidence is further complicated by educational disparities because young Black women with a college degree are 73% less likely to report STI and HIV diagnoses than young Black women without a college degree [26]. Furthermore, having less than a college education may directly influence young Black women’s economic status, by increasing the likelihood of living in poverty.…”
Section: Introductionmentioning
confidence: 99%